La gestión financiera y su impacto en el portafolio de inversiones de la Cooperativa de Ahorro y Crédito Indígena SAC Píllaro Ltda., agencia Guaranda, provincia Bolívar, en el periodo 2015 - 2019 - Lumbi Santillán, Zulema Maribel (2020)
This research project, referred to as financial management and its impact on the investment portfolio of the Cooperativa de Ahorro y Crédito Indígena SAC Pillaro Ltda., Agencia Guaranda, Provincia Bolívar, whose main problem is the scarce information about the investment portfolio, for this, the 2015-2019 periods were taken as a sample, for which an investigation has been carried out from various theoretical perspectives. In order to develop this investigation, the inductive method was used in order to analyze the behavior of the entity's investment portfolios and the deductive method to compare the credits of each period, thus analyzing each of its activities and procedures applied in the institution, in the same way instruments and techniques of information collection were applied, such as an interview directed to the head of agency and a survey directed to the partners of the entity. Through the collection of data and information, the interpretation and analysis of results could be carried out, to continue to make the proposal to formulate strategies that will allow an improvement in financial management and its impact on the Cooperative's investment portfolio